2023
DOI: 10.1111/eci.14082
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sex hormone‐binding protein and non‐alcoholic fatty liver disease using Mendelian randomisation

Jiaming Dong,
Chenming Liu,
Jialiang Lu
et al.

Abstract: BackgroundThe incidence of non‐alcohol fatty liver disease (NAFLD) has been increasing annually with the improvement of living standards. Numerous epidemiological observations have linked sex hormone‐binding protein (SHBG) levels to NAFLD. However, evidence of the causal role of SHBG in the development and progression of NAFLD is still absent. Therefore, a systematic assessment of the causal relationship is needed.MethodA two‐sample Mendelian randomisation (MR) analysis was conducted. Genome‐wide association s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…First, a cross‐sectional design was used, which resulted in limitations in our conclusions regarding the temporal causality. A recent Mendelian randomization analysis showed that the genetic tendency to higher SHBG levels was causally associated with a lower risk of NAFLD, indicating that elevated circulating levels of SHBG provide protection against NAFLD 53 . Future prospective studies are needed to confirm these temporal causalities between sex hormones and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, a cross‐sectional design was used, which resulted in limitations in our conclusions regarding the temporal causality. A recent Mendelian randomization analysis showed that the genetic tendency to higher SHBG levels was causally associated with a lower risk of NAFLD, indicating that elevated circulating levels of SHBG provide protection against NAFLD 53 . Future prospective studies are needed to confirm these temporal causalities between sex hormones and NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…A recent Mendelian randomization analysis showed that the genetic tendency to higher SHBG levels was causally associated with a lower risk of NAFLD, indicating that elevated circulating levels of SHBG provide protection against NAFLD. 53 Future prospective studies are needed to confirm these temporal causalities between sex hormones and NAFLD. Second, regarding the definition of NAFLD, we employed two noninvasive panels for NAFLD in the absence of known causes of other liver diseases or the absence of steatogenic medications, which may underestimate and misclassify the true prevalence of NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning lipid metabolism, the overexpression of SHBG protects against the development of MAFLD, inhibiting hepatic lipogenesis by controlling the main lipogenic enzymes. In this sense, the genetic tendency to high levels of transcription of the hepatokine SHBG was causally correlated with a lower risk of developing MAFLD [138,172]. Therefore, fat accumulation reduces the production of SHBG, increasing hepatic lipogenesis and exacerbating the development of MAFLD [40,43,173].…”
Section: Hepatokinesmentioning
confidence: 99%